A neglected priority? The importance of surgery in tackling global health inequalities - Ewan D. Kennedy; Cameron J. Fairfield; Stuart J. Fergusson (Edinburgh University Global Health Society, 2015)
"I was thinking that I was already dead... now I can talk with you people, I'm so happy! " These words, spoken quietly but with great warmth by a young woman devastated by a vesicovaginal fistula and restored to dignity through compassionate operative treatment, cut cleanly through divides of geography, culture, and class. More eloquently than any statistic she speaks of the life-changing and life-saving importance of surgical services in all health care systems. The woman's testimony features in Jaymie Ang Henry's film, 'The Right to Heal', a deeply moving piece of advocacy that makes a clear case for focusing far greater global attention on the huge need to achieve more equitable access to essential surgery. This is the case we take up here, with a particular focus on the needs of sub-Saharan Africa.